Is democracy still relevant in South African higher education? - Waghid, Y.; Davids, N. (South African Journal of Higher Education, 2022)
At least, over the past four decades post-colonial African higher education has undergone significant changes in the quest to cultivate democratic educational / pedagogical actions in universities. From its early insistence on deliberative action (Waghid 2001), more recently, it assumed the forms of both ethical pursuits (Davids and Waghid 2016) and caring (Waghid 2019). Yet, as South Africa continues its unprecedented transition into a democracy, it is becoming abundantly evident that what is needed in higher education should surpass deliberative, ethical, and caring encounters. The expectation that a democratic climate would ease the deep inequalities in higher education, would somehow set the scene for a renewal of knowledge, and restore opportunities for historically marginalised communities, lies in limbo. Instead, what we witness is the awakening of renewed resistance – this time, not against an unjust apartheid regime, but against a democracy that seems incapable of yielding to its own ideals. In this article, therefore, we argue that for higher education to enact its democratic imperative – that is, its transformative ideals, necessary not only for its own public thriving, but for its citizenship – it ought to invoke the idea of resistance (Davids and Waghid 2021).